Influence of Electronic Modules on Environmental Literacy in Raising Environmental Awareness among Fifth Grade Elementary School Students - Ai Nina Karlina Puspitasari; Mubarok Somantri (Jurnal Elementaria Edukasia, 2026)
This study aims to test the effectiveness of the ecoliteracy e-module in improving elementary school students' conceptual understanding and pro-environmental behavior, particularly regarding waste management and environmental awareness. The background of this study is the limited learning media that can comprehensively and contextually integrate ecological knowledge, attitudes, and behavioral aspects into elementary school learning. The ecoliteracy e-module was developed as an alternative digital teaching material. It is interactive, contextual, and suited to the characteristics of elementary school students. This study used a pre-experimental design with a quantitative approach. It involved one group of students who received treatment without a comparison group. Data collection techniques included pretests and posttests to measure students' understanding. Structured observations were used to identify changes in student behavior in waste management in the school environment. Data analysis focused on comparing scores before and after using the e-module and interpreting findings from behavior observations. The results showed a significant increase in student understanding after using the ecoliteracy e-module. The average pretest score increased by 19.20 points in the posttest. This indicates that the e-module helps students better understand waste management and environmental issues. However, observations indicate that these gains in understanding have not led to consistent behavioral changes. Students' behavior in sorting waste and reducing single-use plastics still varies significantly between individuals. Based on these findings, it can be concluded that the ecoliteracy e-module is effective in improving elementary school students' understanding of waste management and environmental awareness.